Resolving China's Zombies : Tackling Debt and Raising Productivity - Lam, W. Raphael (IMF Working Papers; Working Paper ;, 2017)
Nonviable 'zombie' firms have become a key concern in China. Using novel firm-level industrial survey data, this paper illustrates the central role of zombies and their strong linkages with stateowned enterprises (SOEs) in contributing to debt vulnerabilities and low productivity. As a group, zombie firms and SOEs account for an outsized share of corporate debt, contribute to much of the rise in debt, and face weak fundamentals. Empirical results also show that resolving these weak firms can generate significant gains of 0.7-1.2 percentage points in long-term growth per year. These results also shed light on the ongoing government strategy to tackle these issues by evaluating the effects of different restructuring options. In particular, deleveraging, reducing government subsidies, as well as operational restructuring through divestment and reducing redundancy have significant benefits in restoring corporate performance for zombie firms.